Offsite manufacturing: the way forward for Nigeria's housing industry - Kalo, Shaba James; Rahimian, Farzad Pour; Goulding, Jack Steven (Faculty of Design & Architecture, Universiti Putra Malaysia, 2014)
Nigeria is one of the most developed countries in Africa, with construction contributing to approximately 9% of its Gross Domestic Product. From a housing perspective, new initiatives are now being explored, one of which is Offsite Manufacturing (OSM). Globally, the OSM market uses several terms interchangeably, the most prevalent of which include: prefabrication, offsite production, industrialised building systems, dry construction, modern methods of construction etc. These collective approaches have been successfully used in many countries as means of improving housing delivery, particularly in countries like the UK, USA, Australia, Sweden, Japan and Malaysia. Despite the myriad of benefits associated with OSM (e.g. speed of construction, improved quality, reduced risk etc.), there are various barriers identified in the course of adopting OSM; some of these barriers include: client resistance, lack of established codes and standards, negative perception etc. Given these opportunities and barriers, this study investigates the feasibility of adopting OSM and ways of overcoming the barriers hindering its uptake in Nigeria based on the experiences of developed countries. The first part of this paper presents a synthesised literature review which explores the benefits and challenges of using OSM in different countries (including Nigeria as a comparator). Research findings highlight core OSM uptake barriers, including issues such as: reluctance to innovate, paucity of codes and standards, lack of guidance and information, high capital cost, supply chain integrations, skill requirements etc. Whilst many of these countries have now established strategies to offset these uncertainties, it was also observed that governmental support was pivotal in helping to establish OSM as a viable alternative to traditional approaches. From a Nigerian context, similar parallels are observed, most notably the need to encourage OSM through greater awareness, better government policies, and through skilled supply chain partners in order to help improve the problem of housing shortage.